Using of Some Bacterial Species to Treat Polluted Soils with Hydrocarbons. - AL-Mayaly, I.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Three bacterial species were isolated from three polluted soils with gasoline which leaks from electricity generators that used in different regions in Baghdad; the regions choices to collect the polluted soils were (Al-Shaab, Al- Jadryia and Al-Saydiya). The bacterial species were identified according to international biochemical methods. It was found that these species were Escherichia coli, Enterobacter aerogenes and serratia marcesens. It was found that the optimum temperature and pH were 37CÂ°and 9 these were to cultivate E.coli and S.marcesens, while for E.aerogenes were 25 CÂ° and 9. FTIR (Fluori Transmission Infra Red) spectrum technique was depended to test the ability of isolated bacteria to biodegrade the gasoline in order to use these bacteria in bioremediation for polluted soils with hydrocarbons